Community of philosophical inquiry as a method in early bioethical education - Ćurko, Bruno (Array, 2020)
‘Community of inquiry’ is a concept introduced by Charles Sanders Peirce, and was originally restricted to the practitioners of scientific inquiry. M. Lipman (2003) expanded this concept by moving it into a broader setting – the classroom. He converted the classroom into a community of inquiry, in which “students listen to one another with respect, build on one another’s ideas, challenge one another to supply reasons for otherwise unsupported opinions, assist each other in drawing inferences from what has been said, and seek to identify one another’s assumptions.” David Kennedy (2012) claimed how “Lipman, taking a cue from his friend and mentor Justus Buchler, developed and called ‘community of philosophical inquiry’— the most appropriate way to practice with students the philosophical curriculum that he had developed. This idea is also a philosophical one, and it has a farreaching implication, both practical and theoretical – for learning theory, for theory of teaching, for argumentation theory, for theory of knowledge, for group psychology, for moral education, and perhaps, ultimately of the greatest importance, for grounded political theory and practice.” In various and different approaches to philosophy with children, we can find a community of philosophical inquiry as one of the main methods. For instance, a community of philosophical inquiry is one of the methods used in Ethics and Values Education: “The term ethics and values education (EVE) applies to all aspects of education which either explicitly or implicitly relate to ethical dimensions of life and are such that can be structured, regulated and monitored with appropriate educational methods and tools.” (Strahovnik, 2015). Leaning on the cited definition of EVE, if we focus specifically on the issues of the contemporary world with its ecological crisis and rapid digitalization, we can set the relation of the ethical dimensions of life as a bioethical question.